2019
DOI: 10.3390/rs11151746
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns and Phenology of Tropical Vegetation Solar-Induced Chlorophyll Fluorescence across Brazilian Biomes Using Satellite Observations

Abstract: Solar-induced fluorescence (SIF) has been empirically linked to gross primary productivity (GPP) in multiple ecosystems and is thus a promising tool to address the current uncertainties in carbon fluxes at ecosystem to continental scales. However, studies utilizing satellite-measured SIF in South America have concentrated on the Amazonian tropical forest, while SIF in other regions and vegetation classes remain uninvestigated. We examined three years of Orbiting Carbon Observatory-2 (OCO-2) SIF data for vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 140 publications
(249 reference statements)
2
20
0
Order By: Relevance
“…SIF-fPAR temporal mismatches were found in 2015 [13], where the land surface temperature (proxy for PAR) and nadir BRDF (bidirectional reflectance distribution function) adjusted reflectance (NBAR) in the near-infrared band of the MODIS satellite (an fPAR proxy) showed a temporal mismatch with GOSAT SIF across the climate zones in Amazonia. We agree with the implications of previous findings on the seasonality of SIF in the Amazon [13], which showed that there is leaf phenological diversity [63] that cannot be captured at the scale of KG-climate zones [7,29] and biomes [30,44]. Thus, it may be valid to aggregate SIF time-series of retrievals over combined classes of ERs to capture SIF dynamics and magnitude differences.…”
Section: Sif 757 and Fpar Dynamics At The Scale Of Climate Zonessupporting
confidence: 89%
See 4 more Smart Citations
“…SIF-fPAR temporal mismatches were found in 2015 [13], where the land surface temperature (proxy for PAR) and nadir BRDF (bidirectional reflectance distribution function) adjusted reflectance (NBAR) in the near-infrared band of the MODIS satellite (an fPAR proxy) showed a temporal mismatch with GOSAT SIF across the climate zones in Amazonia. We agree with the implications of previous findings on the seasonality of SIF in the Amazon [13], which showed that there is leaf phenological diversity [63] that cannot be captured at the scale of KG-climate zones [7,29] and biomes [30,44]. Thus, it may be valid to aggregate SIF time-series of retrievals over combined classes of ERs to capture SIF dynamics and magnitude differences.…”
Section: Sif 757 and Fpar Dynamics At The Scale Of Climate Zonessupporting
confidence: 89%
“…The phenological variations in Figure 2B have distinctive yearly minimums and maximums which allow one to coarsely characterize each ER-SIF´s signature. Hence, our research findings confirm the great potential of OCO-2 in capturing the inter-biome temporal variability in the SIFs of different South American biome vegetation types [30].…”
Section: Phenological Diversity Of Sif 757supporting
confidence: 79%
See 3 more Smart Citations